PENGARUH PEMBERIAN EKSTRAK RIMPANG KUNYIT (Curcuma domestica Val.) TERHADAP GAMBARAN HISTOPATOLOGIS GINJAL YANG DIINDUKSI ASAP ROKOK PADA TIKUS PUTIH WISTAR - , KURNIATI SARWENDAH ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Cigarette smoke is one source of toxic chemical inducing pathological lesions in kidney indirectly. Chronic cigarette smoke exposure can increase free radicals and other cytotoxic compounds which are nephrotoxic. Curcumin in turmeric extract is expected to have anti-nephrotoxic in the kidney. The aim of this study is to investigate and determine the protective effects of turmeric extract towards renal pathological lesions in rats exposured to cigarette smokes. Twenty male Wistar rats at 3 months old were divided randomly into four groups of 5 each. The KI was the control group, KII was the group given 9 cigarettes smoke per day, KIII was the group given 0, 25% turmeric extract 1 ml per day and KIV was the group given 9 cigarette smoke and 0, 25% extract turmeric 1 ml per day for 60 days. Results of the present study showed that in rats in the group KII had congestion and hidrophic degeneration in kidney. Whereas, rats in groups KI, KIII and KIV had no lesions in the kidney. It is concluded that the turmeric extract (Curcuma domestica Val.) may have preventive effect on the renal lesions. Furthermore, studies in regard to phytopreventive and/or phytotherapeutic mechanism of turmeric exposure againsts pathological lesions due to cigarette smokes need to be more explained.